Interpret Ogoh-ogoh towards Hindu Contemporary Society - Suda, I Ketut; Indiani, Ni Made (International Research Journal of Management, IT & Social Sciences, 2018)
The interpreting of the making ogoh-ogoh based on the perspective of the cultural studies in related to the festival day of the tawur kesanga towards Hindu society in Bali. It recently is an interesting phenomenon to be studied in the academics. Due to the ogoh-ogoh is made as a series for the ceremony of the tawur kesanga lately. It has been a high cost, although, in the literary texts, it does not find the existence of ogoh-ogoh become the completeness of the tawur ceremony itself. Regarding its phenomenon, the author was interested in studying in term of this. The study was intended to interpret the ideology or a truth behind the making of ogoh-ogoh shown of the religious ceremonies. It was conducted applying a qualitative approach included classifying, categorize, understand, and interpret any data or the facts by paraphrase or description, therefore, the conclusion was generally obtained. The results of the analysis were conducted. It can be understood that the making of ogoh-ogoh recently in the Hindu society in Bali, not merely means to cast out of the evil spirits that have been perceived as buta kala by the Hindu society in Bali. However, it was interpreted as a game of the ideology i.e. capitalist ideology. In term of this was evident that the making of ogoh-ogoh lately, no longer using the local materials that can be freely gotten from the surrounding environment, but must be made by lux materials that must be purchased expensive. Thus, it can be concluded that behind the making of ogoh-ogoh related with the ceremony of the tawur kesanga towards Hindu society in Bali lately was initiated by the game of the ideology i.e. capitalist ideology.